BUILDING INFORMATION MODELING (BIM) APPLIED TO DAYLIGHT SIMULATION & ANALYSIS: COMPARISON OF SHADING DEVICE - Saraswati, Dewi; Khaldun, Ibnu; Affiano, Aseptian (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Improving environmental quality in architectural design is crucial in energy efficiency, health, and comfort, directly impacting occupant productivity. In tropical regions, high exposure to solar radiation significantly contributes to increased energy consumption in the building sector, accounting for 36% of total global energy usage. Shading devices are employed as a passive strategy to minimize solar heat gain, maintain thermal comfort, and evenly distribute natural light, reducing reliance on artificial lighting. This study analyzes the impact of different louver types on daylight optimization in shading devices, designed with the same module across various scenarios (louvers at ∠90°, ∠45°, and ∠150°). The research methodology involves computational simulations based on BIM, using Autodesk Revit for prototype modeling, parameter determination, scenario setup, and the Insight Plugin for simulating daylight illuminance (lux) and daylight factor (DF). The results show that the shading device with a 90° louver angle performs optimally in meeting the daylight illuminance standard (300–3000 lux) across various representative dates, achieving a daylight factor (DF) of 3.2%, in line with global standards. The louver angle significantly influences the overall distribution of natural light. This study's limitation is its focus on a single location (Surabaya) and its restriction to three shading device scenarios.